Genetic alcohol sensitivity regulated by ALDH2 and ADH1B polymorphisms is strongly associated with depression and anxiety in Japanese employees. (1st February 2015) - Yoshimasu, Kouichi; Mure, Kanae; Hashimoto, Marowa; Takemura, Shigeki; Tsuno, Kanami; Hayashida, Mariko; Kinoshita, Kenji; Takeshita, Tatsuya; Miyashita, Kazuhisa
Highlights: Association between genetic alcohol sensitivity and anxiety/depression was evaluated among Japanese workers. Low alcohol sensitivity was associated with an increased risk of depression and anxiety especially among non-drinkers. No adverse effects of ALDH2 or ADH1B alone were observed with depression or anxiety. Abstract: Background: Although alcohol-related disorders (ARD) have been shown to be accompanied by comorbid depressive and anxiety disorders, and alcohol metabolic enzyme genes, ADH1B and ALDH2 polymorphisms, have been associated with an increased risk of ARD, no studies have been conducted to evaluate the associations between these genetic polymorphisms and anxiety or depression. Method: A total of 1944 Japanese workers were interviewed regarding their depressive and anxiety disorders, including suicidality, by a brief psychiatric structured interview (MINI). We investigated the relationship of ADH1B rs1229984 and ALDH2 rs671 polymorphism combinations with mental disorder risks. Logistic regression analysis was used to evaluate the associations between those polymorphisms and anxiety/depressive disorders, adjusting for sex, age, and job rank. The degree of alcohol sensitivity was classified into five groups according to the combination of two enzyme genotypes (Group I–V, in order from the lowest alcohol sensitivity). Results: Those with ALDH2 * 1 / * 1 and ADH1B * 1 / * 1 were likely to be at an increased risk of depressive and anxiety disorders as well as ARD. This tendency was more apparent among non-drinkers (OR 9.20, 95% CI 1.66–50.89). No adverse effects of ALDH2 or ADH1B alone were observed with mental disorder risks. Likewise, analyses conducted combining job rank and genetic alcohol sensitivity showed no material associations with such risks. Conclusions: Genetic alcohol sensitivity, especially that with the genotype combination of ALDH2 * 1 / * 1 and ADH1B * 1 / * 1, was significantly associated with an increased risk of depressive and anxiety disorders as well as ARD.